Peculiarities of personality space organization of servicemen with PTSD signs - Koshyrets, Victor; Shkarlatyuk, Kateryna (Psychological Prospects Journal, 2020)
Purpose. The article deals with the peculiarities of personality space organization of servicemen with posttraumatic stress disorder signs. The main directions and approaches to the study of the psychological space concept as well as the impact of traumatic events on personality space organization as a component of a living space structure are identified. Theoretical grounding of the concept of personality space of servicemen is carried out and its psychological peculiarities are empirically studied. Methods. The standardized psychodiagnostic methods "Sovereignty of psychological space" by Nartova-Bochaver, the Patient Health Questionnaire ( PHQ) -9, the posttraumatic stress disorders screening questionnaire (PTSD SQ), the Impact of Event Scale–Revised (IES-R) are used. Results. It has been determined that sovereignty levels of space, body, social relations, things, and values are associated with the appearance of PTSD signs among servicemen. The conducted research allows to ascertain psychological features among servicemen with PTSD signs that negatively affect their daily lives, the processes of adaptation, resocialization, and organization of their personalality space. The low level of psychological space sovereignty shows signs of deprivation, which is manifested in the experience of subordination, alienation, fragmentation of own life and is characterized by difficulties in finding environment objects with which people identify themselves. Conclusions. The research showed that indicators of predisposition to posttraumatic stress disorder are clearly expressed among servicemen with the low level of psychological space sovereignty. That is, the low sovereignty of space, body, social connections, things, and values affects the probability of PTSD signs occurrence among servicemen. The similar relationship is found out between the level of sovereignty and the tendency presence to PTSD: those servicemen who have high level of psychological space sovereignty do not have the pronounced signs of posttraumatic stress disorder. The importance of solving the rehabilitation tasks, early diagnoses and psychocorrection of servicemen to ensure their mental health, as well as for the development of their personality and professional self-realization is demonstrated.